Role of MDCT Angiography in Evaluation of Nontraumatic Subarachnoid Hemorrhage - Shruti Sharma; Suresh K. Toppo; Rajeev K. Ranjan; Anima R. Xalxo; Nisha Rai; Madan K. Sharma; Abhay Kumar (Journal of Pharmacy and Bioallied Sciences)
Introduction: Subarachnoid hemorrhage (SAH) involves the extravasation of blood into the subarachnoid space and is a critical condition with high mortality and morbidity rates. Nontraumatic causes, predominantly ruptured cerebral aneurysms, account for approximately 85% of cases. Early and accurate diagnosis using advanced imaging modalities such as multidetector computed tomography (MDCT) angiography is crucial for effective management. Materials and Methods: A hospital-based cross-sectional study was conducted over 24 months. Forty patients clinically suspected or diagnosed with nontraumatic SAH were evaluated using MDCT angiography. Data included demographics, clinical presentation, and imaging findings, which were analyzed using statistical methods. Results: Among 40 participants, 29 had positive findings on MDCT angiography. Aneurysms were the most common abnormality (65%), predominantly located in the anterior circulation (47.5%). The sensitivity of MDCT angiography was 89.65% compared to non-enhanced CT. Key risk factors included hypertension and smoking. Gender analysis revealed a higher incidence in females (82.3%) compared to males (65.2%). Discussion: MDCT angiography is effective for diagnosing and planning interventions for SAH. It reliably detects aneurysm characteristics, including size, shape, and location, aiding in risk assessment and treatment planning. Its role as a noninvasive alternative to digital subtraction angiography is emphasized. Conclusion: MDCT angiography is a valuable tool in evaluating nontraumatic SAH, providing critical insights for prompt and accurate diagnosis, risk stratification, and therapeutic planning.